PEMBERDAYAAN MASYARAKAT MELALUI BANK SAMPAH DI DESA PERBAWATI KABUPATEN SUKABUMI - Jimatul Arrobi; Cecep Hilman; Chika Chyntia (Institut Madani Nusantara, 2023)
This research aims to understand the benefits of a Waste Bank in empowering the community in Perbawati Village. The study also seeks to identify the factors that influence community empowerment in the village. The results indicate that Waste Bank activities such as awareness campaigns, waste conservation, waste sorting, training, and evaluation have a positive impact on creating a cleaner environment. The Waste Bank also provides additional income for active community members and strengthens social relationships in Perbawati Village. However, there are still several challenges, including poor management performance, unclear task allocation, and low community participation.